Ecthyma Gangrenosum-like Lesions in a Febrile Neutropenic Patient with Simultaneous Pseudomonas Sepsis and Disseminated Fusariosis - Seven Uludokumacı; İlker İnanç Balkan; Bilgül Mete; Reşat Özaras; Neşe Saltoğlu; Teoman Soysal (Turkish Journal of Hematology, 2013)
Fusarium spp. is an opportunistic mold that causes disseminated infections in immunocompromised patients. It is important to make a definite diagnosis because of high mortality rates. We present the case of a 27-year-old pregnant woman diagnosed with acute myeloid leukemia with a prolonged febrile neutropenic period. She developed ecthyma gangrenosum-like lesions and simultaneously had Pseudomonas bacteremia and disseminated fusariosis. Histopathological and microbiological features of skin lesions had a critical role in differential diagnosis. Ecthyma gangrenosum-like lesions due to disseminated fusariosis might be easily misdiagnosed as lesions associated with Pseudomonas unless tissue cultures and histopathological examinations are performed.